1986
DOI: 10.1051/parasite/1986612199
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of ecology and biogeography of Acanthocephala in antarctic seabirds

Abstract: SUMMARY. Four species of acanthocephalans are reported from seabirds, nototheniid fishes and gammaridean amphipods in the western Antarctic. Corynosoma hamanni (von Linstow, 1892) was found in Phalacrocorax atriceps King, Chionis alba (Gmelin), Larus dominicanus Lichtenstein, and Catharacta lonnbergi (Mathews). The complete life cycle of this acanthocephalan was elucidated : cysticanths develop in the haemocoel of a gammaridean amphipod, Pontogeneiella sp. of the family Eusiridae and presumably, following inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…probably have either two or three hosts. Antarctic Amphipoda are recorded as the intermediate hosts of four acanthocephalan species (Hoberg 1986, Zdzitowiecki 2001, Zdzitowiecki and Presler 2001. Zdzitowiecki (1991a) reported that acanthocephalans are common in bottom-living fishes, but absent from pelagic ones.…”
Section: Cestodamentioning
confidence: 99%
“…probably have either two or three hosts. Antarctic Amphipoda are recorded as the intermediate hosts of four acanthocephalan species (Hoberg 1986, Zdzitowiecki 2001, Zdzitowiecki and Presler 2001. Zdzitowiecki (1991a) reported that acanthocephalans are common in bottom-living fishes, but absent from pelagic ones.…”
Section: Cestodamentioning
confidence: 99%
“…Their life cycles typically include a crustacean (amphipod, copepod, or decapod) as an intermediate host and may include fish, snakes, frogs, or toads as paratenic hosts (Schmidt, 1985;Hoberg, 1986;Nickol et al, 1999Nickol et al, , 2002. Polymorphids include approximately 127 species, classified into 11 genera (Schmidt, 1973;Dimitrova and Goergiev, 1994;Nickol et al, 1999Nickol et al, , 2002Aznar et al, 2006).…”
mentioning
confidence: 99%
“…It is possible that parallel rebuilding of parasites took place during the time and could be the reason for an increased number of cystacanths of C. arctocephali in fish (Zdzitowiecki 1987). Zdzitowiecki (1985) and Hoberg (1986) established the gentoo penguin (Pygoscelis papa) as the only final host of C. shackletoni. The abundance of the gentoo penguin population in Admiralty Bay has been fluctuating in the 29 years between the first study and the current one.…”
Section: Resultsmentioning
confidence: 99%
“…According to Palm et al (1998) N. coriiceps plays the important role in life cycles of many different parasites including Acanthocephala. The most important data on the infection of this fish with acanthocephalans were published by Johnston and Best (1937), Szidat (1965), Hoogesteger and White (1981), Hoberg (1986), Zdzitowiecki (1986aZdzitowiecki ( , 1986bZdzitowiecki ( , 2001a, Zdzitowiecki and Rokosz (1986), White (1992, 1996), Palm et al (1998), Rohde et al (1998), Zdzitowiecki et al (1998) and Zdzitowiecki and Laskowski (2004). The most extensive investigations were carried out in two localities at King George Island (South Shetland Islands): in Admiralty Bay (Zdzitowiecki 1986a(Zdzitowiecki , 1986bZdzitowiecki and Rokosz 1986) and in Potter Cove (Palm et al 1998).…”
Section: Introductionmentioning
confidence: 99%